(untitled) (REMUNOM, 2025)
This article analyzes civil liability arising from psychological harm in interpersonal relationships, focusing on cases of moral harassment and bullying. The relevance of this research lies in the need to understand how the Brazilian legal system protects human dignity against practices that directly affect victims’ mental health, extending beyond the financial sphere and affecting personality rights. The central objective is to examine how the 1988 Federal Constitution and the 2002 Civil Code support the recognition and reparation of moral harm, as well as to identify the criteria used by case law to determine the quantum of compensation. The research question is to determine how Brazilian law can adequately recognize and compensate psychological harm, considering the subjectivity of human suffering and the difficulty of measuring fair compensation. The methodology adopted is bibliographical and documentary in nature, allowing us to identify the essential elements of civil liability and assess how legal doctrine and the courts have addressed the issue. It was found that compensation for psychological harm fulfills not only a compensatory function, but also a punitive and educational one, discouraging harmful behavior and promoting the prevention of further violations. It is concluded that the recognition of psychological harm represents a significant advance in the realization of personality rights and in the consolidation of human dignity as the foundation of the democratic rule of law.